La inspección educativa. Potestad, ejercicio y expresión - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2024)
The Spanish Constitution establishes that “the public powers will inspect and standardize the educational system to guarantee compliance with the laws” (article 27.8), delimiting its extension, responsibility and role.Organic Law 2/2006, of May 3, on Education, establishes that “the educational inspection will be carried out on all elements and aspects of the educational system, in order to ensure compliance with the laws, the guarantee of rights and the observance of the duties of those who participate in the teaching and learning processes, the improvement of the educational system and the quality and equity of teaching” (article 148.3, modified by section 1 by sole article.77 bis of Organic Law 3 /2020, of December 29) and “the high inspection and other powers that, in accordance with article 149.1.30. of the Constitution, correspond to guarantee compliance with the obligations of the public powers” ​​(article 149, modified by the sole article 77 ter of Organic Law 3/2020, of December 29).It is interesting, then, to analyze the attribution, performance and delimitation of the educational inspection based on its power, exercise and expression.